ICT in Education:The Changing Role of Teachers - Markovac, Vesna (Array, 2007)
Abstract Computers and Internet connections are becoming widely available in schools and classrooms. The new learning environments demand new teaching and learning skills. Worldwide, many countries are making the creation and diffusion of information and communications technology (ICT) an important priority. As ICT becomes more widely available, teachers and policymakers are turning their attention to the difficult task of understanding how best to integrate this technology into learning environments. ICT can be used in many different ways, and how it is integrated into educational settings depends largely on teacher's instructional goals and strategies. Changes in the goals of education during the latter part of the twentieth century, coupled with increases in the amount and type of available technology, has created changes in teachers' use of technology. It has big impact on teachers and teaching. Introducing ICT in education is challenge for teachers and pupils. Teachers have to develop their own ICT skills and change their existing practices. The role of teching is changing. Successful integration into the curriculum depends on teachers being convinced of the relevance of ICT as a means of providing access to a richer range of resources for themselves and pupils.